Teachers' improvement in educational and learning design for slides production - Sbrogio, Renata de Oliveira (2022)
The present study shows the results of an Action-Research carried out with teachers from private and public education, working from kindergarten to high school in Brazil. The course based on physical attendance and on-line involvement which was entitled "Education and Learning Design: Production of Learning Objects” was performed in 2019, and its main objective was to teach general concepts and fundamental principles related to graphic and learning design for slides. We believe that these factors lead participants to a new perspective about the content production routine, which is more visually exciting and suitable for their students' learning. We chose an Action-Research methodology because it was possible to analyze more subtle nuances of advances that occurred among the observed teachers. The improvement in the visual communication promoted by the learning objects produced by the participants, especially the lesson slides, demonstrates that the knowledge related to education and learning design is essential in teaching practice.